ФОРМУВАННЯ ЦІННІСНИХ ОРІЄНТАЦІЙ ВЧИТЕЛІВ У ПРОЦЕСІ ПРОФЕСІЙНОЇ ПЕРЕПІДГОТОВКИ (Педагогіка вищої та середньої школи, 2009)
The notions of "value orientations" essence is revealed, professional value orientations particularities of the teacher are characterized, content, structure and mechanism of it's formation is explored in the article. It has been selenpically motivated pedagogical conditions for the professional value orientation of the wachers which favoured de vastly increasing the formation value orientation level among teacher.